2019
DOI: 10.7554/elife.46409
|View full text |Cite|
|
Sign up to set email alerts
|

The manifold structure of limb coordination in walking Drosophila

Abstract: Terrestrial locomotion requires animals to coordinate their limb movements to efficiently traverse their environment. While previous studies in hexapods have reported that limb coordination patterns can vary substantially, the structure of this variability is not yet well understood. Here, we characterized the symmetric and asymmetric components of variation in walking kinematics in the genetic model organism Drosophila. We found that Drosophila use a single continuum of coordination patterns without evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(180 citation statements)
references
References 108 publications
14
160
0
Order By: Relevance
“…Eventually, mirror image patterns are possible with phase coupling among contralateral legs deviating from phase values of 0.5. Patterns recently described as non-canonical by DeAngelis et al (2019) can be observed, too (e.g. Fig 3C).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Eventually, mirror image patterns are possible with phase coupling among contralateral legs deviating from phase values of 0.5. Patterns recently described as non-canonical by DeAngelis et al (2019) can be observed, too (e.g. Fig 3C).…”
Section: Discussionmentioning
confidence: 52%
“…As has been shown neuroWalknet is able to produce footfall patterns that include "tripod" patterns, "tetrapod" patterns, "pentapod" patterns as well as various stable intermediate patterns. These patterns form a continuous multitude as has been observed in stick insects (Graham 1972) and in Drosophila (Wosnitza et al 2013;DeAngelis et al 2019) and to some extent in cockroaches (e.g. Hughes 1952;Bender et al 2011).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Critically, high resolution analyses of walking gait in freely walking flies revealed that BPN-TeTx flies were not uncoordinated ( Figure S7) but instead walked slowly as a result of an increased step period, specifically due to an increased stance duration ( Figure 7E). Previous work has shown that flies typically vary walking speed by varying stance duration (DeAngelis et al, 2019;Wosnitza et al, 2013). Therefore, the gait of BPN silenced flies resembles that of slow walking flies.…”
Section: Bpn Activity Reciprocally Regulates Straight Forward Walkingmentioning
confidence: 97%
“…Here, we use in vivo calcium imaging, whole-cell patch clamp electrophysiology, and optogenetics during walking behavior to investigate motor control of the Drosophila tibia (Figure 1A). The femur-tibia joint of a walking fly flexes and extends 10-20 times per second, reaching swing speeds of several thousand degrees per second (DeAngelis et al, 2019;Gowda et al, 2018;Mendes et al, 2013;Strauss and Heisenberg, 1990;Wosnitza et al, 2013). Flies also use their legs to target other body parts during grooming (Hampel et al, 2015;Seeds et al, 2014).…”
Section: Introductionmentioning
confidence: 99%